Gambaran Karakteristik dan Praktik Petugas Puskesmas Dalam Penemuan Kasus Tuberkulosis Paru di Kabupaten Magelang - Rahayu, Atik; Wuryanto, Moh Arie; Martini, Martini (Jurnal Riset Kesehatan Masyarakat, 2023)
Case Detection Rate of pulmonary Tuberculosis in Magelang District still low. The purpose of this research is to gain characteristics and practices of Public Health Center on case finding of pulmonary tuberculosis in Magelang District in terms of aspects of age, gender, level of education, level of knowledge, length of employment, perception of workload, training history, contact tracing, counseling, networking and practical cases of laboratory officer. This research is a descriptive study. The population is all Pulmonary tuberculosis programs officers in 29 Public Health Center in Magelang District. The total samples are 87 officers, consist of 29 P2TB officers, 29 laboratory officers, 29 medics and paramedics. The sampling technique is purposive sampling. Median of age of P2TB officers is 44 years, mean of medics and paramedics is 39.2 years, and median of laboratory officer is 30 years. Most of respondents are female and background in college-level education. Mean of the length of working for P2TB officer is 9.7 years, median for laboratory officer is 4 years, and median for medical officer and paramedics are 4 years. 79.3% of P2TB officers and 93.1% of medical officers and paramedical had a training history of < 2 training. The level of knowledge of P2TB officer 51.7% in poor category. Contact tracing of P2TB officer 41.4% in poor category. Counseling of P2TB officers 41.4% in poor category. The entire laboratory officer practice fixation and staining in both categories. Networking cases of medical and paramedical staff 51.7% in poor category. Perception workload of medical and paramedical officer 51.7% in weight category. Suggestions for Magelang District health department is that the department should expand networking case by cooperating with private practice doctors and give a priority for officers who have been trained yet to be included in the training on Tuberculosis.